Chronic eczema developing over skin treated for dermatophytosis in atopic patients -Importance of treating gently and intelligently - Shyam Verma; Ramkumar Ramamoorthy; J Vasani Resham (Wolters Kluwer Medknow Publications, 2022)
A novel observation of chronic eczema developing over the skin of adequately treated lesions of tinea cruris/tinea corporis in six atopic individuals is being shared. We propose that the skin of atopic individuals affected by dermatophytosis be observed for secondary changes even after the complete resolution of the lesions. The use of bland emollients with topical antifungal agents should be encouraged in atopic patients. The extent and duration of the compromised epidermal barrier function of the skin of atopic individuals with dermatophytosis need to be studied further.